PENINGKATAN KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA MELALUI MODEL CREATIVE PROBLEM SOLVING DI KELAS V SDN 225/II PELEPAT LINTAS - Rifa Putri Chodilah; Nurlev Avana (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to describe the application of the Creative Problem Solving (CPS) learning model to improve students’ abilities and learning processes in solving mathematical story problems. The research used a Classroom Action Research (CAR) approach, consisting of planning, implementation, observation, and reflection conducted over two cycles. Each cycle included two meetings. The data were collected through observation sheets, learning outcomes tests, and field notes. The results showed that the CPS model significantly improved students’ problem-solving abilities. The percentage of students achieving mastery increased from 62.5% in cycle I to 81.25% in cycle II. Likewise, the learning process became more active and engaging through collaborative and contextual problem-based learning.